Hermeneutika Eksistensial Transendental Mullâ Shadrâ: Mencari Akar Fundamental Moderasi Beragama - Abdul Muid Nawawi; Mulyani Mulyani (Tafhim Al-'Ilmi, 2023)
Many human tragedies arise from religious extremism. This paper seeks to explain and provide an argument that the root of the problem of religious extremism lies in the failure to recognize the essence of religion and its equality with humanity itself. In the context of Islam, through the hermeneutics of Mulla Shadra this paper attempts to explain that the Qur'an, man and nature are three aspects of a single existential reality. This introduction brought all three to the peak of their sacred and perennial dimensions so as to anticipate religious extremism in terms of genealogy of consciousness. The philosophical hermeneutic approach becomes the path of contemplation of reasoning of this paper which is a blend of the methodology of Henry Corbin and Mulla Shadra. Keyword: Transcendental existential hermeneutics, human tragedy, religious extremism